Traveling waves in a nonlocal dispersal SIR epidemic model. (June 2015) - Yang, Fei-Ying; Li, Wan-Tong; Wang, Zhi-Cheng
Abstract: This paper is concerned with traveling wave solutions of a nonlocal dispersal SIR epidemic model. The existence and nonexistence of traveling wave solutions are determined by the basic reproduction number and the minimal wave speed. This threshold dynamics are proved by Schauder's fixed point theorem and the Laplace transform. The main difficulties are that the semiflow generated by the model does not have the order-preserving property and the solutions lack of regularity.